Review of the recent progress on thermal conductivity of nanofluid - Lenin, Ramanujam; Joy, Pattayil Alias; Bera, Chandan (Journal of Molecular Liquids, 2021)
Thermal properties of nanofluids are very well investigated by the global research community for their various applications. The dispersion and stability of the nanoparticles in the base fluid are the essential requirements for the efficient utilization of nanofluids in many applications. The interfacial layer plays a crucial role in the dispersion, stability, and heat transfer properties of the nanofluid. The heat transfer property of the nanofluids is mainly influenced by the heat transfer properties at the particle-fluid interface. The thickness and thermal conductivity of the interfacial layer are the crucial factors that decide the heat transfer at the interface, and the difficulties in the determination of these factors limits the progress of the research. In this review article, the experimental studies on the thickness and thermal conductivity of the interfacial layer are reviewed briefly. The effect of interfacial the layer on the nanoscale mechanisms and thermophysical properties of nanofluids are reviewed. The effect of various tunable parameters on the heat transfer properties of the interfacial layer is also reviewed. This review will be beneficial for fine-tuning nanofluid's thermal properties and their commercial applications. (C) 2021 Elsevier B.V. All rights reserved.
Keywords: Interfacial layer; Interfacial thermal conductance; Nanofluid; Surfactants; Thermal conductivity